The Biggert-Waters Flood Insurance Reform Act of 2012: Temporarily Curtailed by the Homeowner Flood Insurance Act of 2014—A Respite to Forge an Enduring Correction to the National Flood Insurance Program Built on Virtuous Economic and Environmental Incentives - Alexander B. McDonnell (Washington University Journal of Law & Policy, 2015)
In the wake of Hurricane Sandy in 2012, this note challenges the economic and environmental efficiency of the National Flood Insurance Program (NFIP) as it stands, and as it relates to the Biggert-Waters Flood Insurance Reform Act of 2012 (Biggert-Waters). The NFIP, which was enacted to provide flood insurance at low costs to coastal dwellers, was modified by Biggert-Waters, an act to help NFIP manage its debt by increasing insurance premiums to property owners, among other things. This note argues that as Biggert-Waters has been overshadowed by the Homeowner Flood Insurance Affordability Act of 2014, Congress is in a unique position to legislate in a manner that can more effectively balance the interests of coastal property owners, the environment, and the NFIP.
Keywords: flooding; environment; flood insurance